X-ray diagnostics of tuberculosis in the screening of patients with HIV infection - E. A. Borodulina; A. N. Kuznetsova; B. E. Borodulin (Acta Biomedica Scientifica, 2023)
Background. The main method of screening of patients with HIV infection to detect pulmonary tuberculosis is X-ray diagnostics. A comparative assessment of changes in lung tissue in different methods of X-ray diagnostics and at different levels of CD4+ cells seems relevant.The aim of the study. To compare plain radiography and computed tomography of the lungs as screening methods for detecting tuberculosis in patients with HIV infection at various stages of immunosuppression.Materials and methods. 396  patients with HIV registered at the AIDS Center were  examined using plain lung radiography (PLR) and computed tomography (CT). To search for mycobacterium tuberculosis, we used bacterioscopy of a smear with Ziehl – Neelsen staining; HAIN-GenoType MTBDRplus technique; inoculation of BACTEC MGIT 960 liquid media; inoculation of Löwenstein – Jensen dense medium. Statistical processing of numerical material was carried out using the Statistica 5.5 program with a significance level p ≤ 0.05; Pearson χ2 criterion was used for the analysis of qualitative featuresResults. When comparing the results of PLR and CT, the differences were found. When  using PLR, the focal lung lesions were described more often (χ2  =  40.79; p = 0.00001), according to CT data, they turned out to be fibrosis (χ2 = 2.33; p = 0.1269). When comparing the PLR and CT data, the differences were obtained in the description of pulmonary fibrosis (χ2 = 20.78; p = 0.00001), focal lung lesions (χ2 = 40.79; p = 0.00001), dissemination (χ2 = 9.16; p=0.0025).Conclusion. When screening HIV-infected patients (at the standard of using plain radiography twice a year) it should be taken into account that CT provides more precise differentiation of focal lung lesions and pulmonary fibrosis, earlier detection of dissemination syndrome and ground-glass, especially at severe immunodeficiency with a decrease in CD4+ T lymphocytes down to 200 cells and less. Timely appointment of CT study will improve the effectiveness of tuberculosis detection at the stage of screening in AIDS centers.